PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN SIAK GROSIR PEKANBARU - Husni Fuaddi; Rahmat Febriansyah (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to determine the effect of work discipline on the performance of Siak Grosir Pekanbaru employees. The sample in this study were employees at Siak Grosir Pekanbaru, totaling 60 people. While the variables examined in this study are work discipline and employee performance. Data analysis used a simple linear regression method using validity, reliability, normality tests, R2 tests and t tests. The test is carried out in order to determine the relationship between the independent variable (independent variable) and the dependent variable (the dependent variable). Based on the results of the study, work discipline simultaneously influences employee performance with a correlation value of R=0.495 which indicates a close relationship between work discipline and employee performance at Siak Grosrir Pekanbaru. While the R square is 0.245, which means that work discipline has a balance contribution of 24.50%. While the remaining 75.50% is influenced or explained by other variables not included in the research model. Partially, it was obtained that the work discipline variable had a positive and significant effect on the performance of Siak Grosir Pekanbaru employees with t count. It can be seen that t count 4,341 > t table 2,001 with a significant 0.000 smaller than alpha 0.05. The simple linear regression equation in this study: Y = 14,792 + 0.390X.